(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Implementation of the concept of sustainable development gives grounds to state the existence of changes in the qualitative and quantitative characteristics of the activities of individual entities, their associations, branches, etc. Such changes are due, first of all, to changes in the parameters by which various entities characterize their strategic, current and operational goals. Another factor changes in the behavior of economic agents are changes in the characteristics of the information on which decisions are made. The implementation of such decisions contributes to the achievement of relevant goals. Takes on particular relevance to evaluate compliance data generated and used for decision-making, a number of critical values (criteria). Such criteria, in our opinion, should be determined by a set of parameters, the content of which will give grounds to determine the degree of reliability of data and their ability to facilitate the realization of expectations of users of information. One of the mechanisms for evaluating such compliance is the implementation of control measures, one of the forms of which is an audit. The main factors of formation of evaluation criteria of information which can be used during the audit are considered. It is established that the process of forming the criteria for evaluating information is influenced by the interests of its users, the strategic, tactical and operational goals of users, as well as their expectations for the formation, content and use of information. It is also important to consider when determining the criteria for evaluating information in the conditions of sustainable development of the impact of the environment of the functioning of economic entities that produce and use information for their own purposes. The results of the research identified the impact of the internal environment, the environment and the integrated (reflexive) impact of sustainable development on the formation of criteria for evaluating information.